Identifying patterns of alumni commitment in key strategic relationship programmes - Pedro, Ilda (2021)
Higher education institutions (HEIs) need to understand their alumni when drawing strategic relationship programmes. This paper aims to identify clusters of alumni based on their commitment relationship and to analyse factors influencing their intention to collaborate with the HEI. The study took place at a Portuguese university, considering a dataset of 1075 of alumni asserting intention to collaborate. First, a cluster analysis was conducted to identify patterns of commitment relationship. Secondly, a logistic regression was run to identify determinants of intention to collaborate. Both techniques revealed the decisive role of HEI commitment in the process. Relationship advantages and positive feelings towards the HEI were also pointed out as important. Alumni asserted recommendations, further training, sharing experiences and giving help as ways to collaborate with HEI. Regression results suggest that sociodemographic variables such as gender, marital status and volunteering are significantly associated with a probability to collaborate. Results also show that affiliation in sororities/fraternities and participation in extracurricular activities are significantly associated with that collaborative intention. The findings provide clues to support strategic relationship programmes based on consistent marketing campaigns, while bringing value to the literature in the European context, where alumni culture requires real insights to evolve.